Multidimensional Determinants of Well-Being Among Community-Dwelling Older Adults During the Early Stage of the COVID-19 Pandemic in Taiwan. (July 2022) - Chen, Jia-Jen; Liu, Li-Fan; Lin, Chung-I; Lin, Heng-Chun
Objectives: Due to the insufficient and inadequate policies on the psychological well-being of the aged population, we aimed to examine the multidimensional determinants of well-being during the early stage of the COVID-19 pandemic.Method: Data were collected from face-to-face interviews with1, 232 participants aged 50 and older living in Southern Taiwan. We used multivariate logistic regression to examine the associations between demographics, the physical health, mental health, social ties domains, and well-being.Results: We found that (i) in physical health, no dental problems and exercise were related to better well-being; (ii) in mental health, stress and depression decreased well-being, but laughing every day, and a positive attitude toward aging had adverse effects; and (iii) in social ties, subjective social status, family support, and place attachment to the community were positively associated with well-being.Discussion: Our findings highlight the multidimensional needs at the individual and community levels for the Chinese population.